Germination of seeds of some local pioneer plant species in different hydroseeding mulches for revegetation of post-coal mining soil - D Azaila; C Retnaningdyah; E Arisoesilaningish (Journal of Degraded and Mining Lands Management, 2016)
The purpose of this study was to determine the hydroseeding mulch optimum compositions for germination and productivity of a few species of local plants pioneer in the post-mining land of coal from South Kalimantan. The method used in this research was by hydroseeding technique. The species observed were Crotalaria pallida, Cajanus cajan, Kyllinga monocephala, Paspalum conjugatum, Digitaria sanguinalis and Eleusine indica. Seven variations of mulch were added to the post-mining soil. Planting seeds carried out were monoculture and polyculture. Each composition of mulch was replicated three times resulting in 147 pots. Seed germination was observed  for 15 days. The results showed that all species were able to germinate and and grow well in the mulch that was added to the post-mining soil, except Kyllinga monocephala on mulch two, four and five and Digitaria sanguinalis on mulch four. The best mulch for plant growth was characterized by pH of 6.8-7.0, 47-59% organic matter, and energy ranging from 2,337.68 to 3,792.68 Kcal/kg. The highest percentage of germination was observed for Cajanus cajan (56.7%) and Crotalaria pallida (39.4%) on mulch two with germination time of eight and three days after planting. The lowest germination percentage was shown by Kyllinga monocephala at all mulch treatments (up to 30 days after planting). The optimum composition of mulch that could be recommended to accelerate the revegetation was mulch two (pH 7.06 and 59% organic matter), especially for Leguminosae, and mulch seven (pH 6.8 and 47% organic matter), especially for Poaceae and polyculture.